Analysis of Barriers in the Implementation of the Slum-Free City Program in Lhokseumawe City, Aceh Province - Riski, Aflia; Mujiburrahman, Mujiburrahman; Meliza, Richa; Hafni, Nur (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
The Slum-Free City Program is one of the strategic initiatives by the Indonesian government aimed at reducing slum areas in urban regions and improving the quality of life for the community. The establishment of Qanun Lhokseumawe City No. 11 of 2018 has made the Slum-Free City Program an effort to address slum settlement issues in Lhokseumawe City. This study aims to analyze the barriers faced in the implementation of the Slum-Free City Program in Lhokseumawe City. The research method used is qualitative with a descriptive approach, and the data were collected through interviews, observations, documentation, and literature review. The results of the study show that the barriers in the implementation of this program include insufficient budget allocation to meet all program needs, social, economic, and cultural constraints within the community, technical and infrastructure challenges, low public participation and awareness regarding the importance of cleanliness and supporting the Slum-Free City Program, and a lack of coordination among the various institutions (government, NGOs, and private sector) involved in the program. Additionally, legal issues related to land ownership and the limitations of regulations that support the Slum-Free City Program are also significant barriers. Based on these findings, the recommendations include increasing budget allocation, strengthening inter-agency coordination, improving socialization and education for the community, and enhancing technical and administrative mechanisms. This research is expected to contribute to improving the implementation of the Slum-Free City Program in the future and help realize cities free from slum areas.